Role of early debridement in non-healing ulcer - Tote, Darshan; Jajoo, Suhas; Tote, Sachin (International Surgery Journal, 2017)
Background: Non-healing wound is a commonly encountered entity with a broader effect on both the sufferer and the treating doctor. Time taken in healing these wound is directly related to financial loss as well as loss of working hours, thus ultimately increasing the financial burden. Chronic wound has devitalized tissue at the base which is barrier to cell migration and acts as supportive environment for bacterial growth. Considering the effect of devitalized tissue on wound healing there lies importance of debridement in wound management. Debridement is an effective technique to achieve desirable wound bed preparation by removing the dead and devitalized tissue. Hence a study was conducted at a rural hospital with main aim to assess role of surgical sharp debridement in non-healing wound in complete healing or preparing wound for further definitive treatment. Methods: The study was conducted at AVBRH Sawangi (Meghe), Wardha. Random 50 patients of non-healing ulcer were selected for the study. One group was of early debridement while other group of dressing with moist dressing only. Wound were assessed for healing, wound contraction, scar quality at regular intervals. They were assessed for duration of wound to heal completely/ get ready for further intervention like SSG/ Flaps, Cost of treatment and Time taken by the patient to return back to work. Results: 36% of patients in moist dressing group heal completely by 4 weeks while 56% of patients in debridement group heal completely by 4 weeks. Early recovery leads to early normalcy so less loss of wages and thus making the group cost effective. Conclusions: Early debridement was found to be an effective tool in wound healing in non-healing ulcers.